(3TQM CHjGJ GdLeds - (3eMeO Hf CMeO Hf gTGe Hf Nda GddNej GdCfOdSj, CHh YHO Gddg,J (B577 (3g` s; (3YHO GdbGgQ Hf YHO GdQMef Hf eMeO GdLQLGfj, CHh HcQ,J (B471 (3g` s
(3ChdgG (B:s
(3bGdhG aj HYV CHjGJg CfgG eLghdI, hgj eYdheI hbUQgG Ydi ZjQ eG CQGOg GdWGYf hbdI QhGjGJge ddbUGFO GdJj CNPJ efgG s
(3BNQgG (B:s
(3hJhai GdaQROb QMeg Gddg ef PGJ GdLfH, hbGd LQjQ jQKg hdg CjVkG jQKjg hde jdHK LQjQ HYOg EdG CTgQ fLR GdcJGH s
(3fSNI ajgG VHW hHgG CKQ JbWjY hWeSs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdfMhs